Geotechnical properties of natural sand-mixed granulated blast furnace slag applied to the sand compaction pile method - Nguyen Thi Thanh, Nhan; Matsuda, Hiroshi; Duong Trung, Quoc; Tran Xuan, Thach; Tran Thi Phuong, An; Tran Thi Ngoc, Quynh; Tran Thanh, Nhan; Pham Van, Tien; Nguyen Thi Le, Huyen (Vietnam Journal of Earth Sciences, 2023)
Granulated blast furnace slag (GBFS) has more advantageous properties over natural sand, such as lightweight, higher shear strength, and higher permeability. Therefore, it is regarded as a potentially promising substitute for natural sand in the ground improvement using the sand compaction pile (SCP) method. Due to the relatively rapid solidification, however, which is induced by the latent hydraulic property of GBFS, the permeability of the installed GBFS compaction pile (GBFSCP) decreases quickly, and such an application becomes difficult for the case of SCP with low sand replacement area ratio (LSRAR). So, to decelerate the permeability reduction of GBFSCP, different GBFSs, and natural sands were collected in Japan and Vietnam, and the specimens were prepared by changing the mixing ratio of sand to GBFS from 20% to 80%. Then, firstly, fundamental geotechnical properties of sand-mixed GBFS without hydration were observed. Secondly, the specimens of sand-GBFS mixture were cured in seawater at the temperature of 80°C for 3 days to 380 days. The unconfined compressive strength, permeability, and hydration reaction rate of the hydrated sand-mixed GBFS specimen were measured. In conclusion, the geotechnical properties of the unhydrated sand-mixed GBFS become more advantageous than those of natural sand. In addition, by mixing with natural sand, the hydration reaction rate and the solidification of GBFS are controlled. This means that it is possible to keep the compressive strength and the permeability at the predetermined conditions and, in turn, to satisfy requirements for the SCP method with LSRAR. In addition, a simple estimation method of the unconfined compressive strength was proposed for the hydrated sand-mixed GBFS specimen.